Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jvh.12981
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in mortality for chronic liver disease among Asian subpopulations in the United States from 2007 to 2016

Abstract: The Asian American population is characterized by remarkable diversity. Studying Asians as an aggregate group may obscure clinically meaningful heterogeneity. We performed a population-based study using data from the US National Vital Statistics System. We determined the trends in age-standardized mortality rates for chronic liver disease stratified by aetiology among the most populous US-based Asian subgroups (Asian Indians, Chinese, Filipino, Japanese, Korean and Vietnamese) and compared it to non-Hispanic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Prevalence ratios (PRs) were estimated by modified Poisson regression models with sandwich error variance while adjusting for age, sex, and race/ethnicity. The population counts for Hispanic and Asian American subgroups in non‐Census years were estimated by linear interpolation (2008‐2009), U.S. Census data (2010), and extrapolation (2011‐2016), using the 2000 and 2010 U.S. Census reports . Joinpoint trend analysis was run with the JR Program, version 4.5.0.2, from SEER, and all other analyses were performed with SAS software, version 9.4 (SAS Institute, Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence ratios (PRs) were estimated by modified Poisson regression models with sandwich error variance while adjusting for age, sex, and race/ethnicity. The population counts for Hispanic and Asian American subgroups in non‐Census years were estimated by linear interpolation (2008‐2009), U.S. Census data (2010), and extrapolation (2011‐2016), using the 2000 and 2010 U.S. Census reports . Joinpoint trend analysis was run with the JR Program, version 4.5.0.2, from SEER, and all other analyses were performed with SAS software, version 9.4 (SAS Institute, Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
“…According to a population‐based study using the US Census and national mortality database, age‐standardized cirrhosis‐related mortality rates increased from 19.77/100 000 persons in 2007 to 23.67 in 2016 with an annual increase of 2.3% (95% confidence interval 2.0–2.7) . Mortality caused by cirrhosis was approximately threefold higher among non‐Hispanic whites than all Asians . Hispanic and Asian patients reported to have a higher risk of developing cirrhosis and HCC compared to Caucasian patients .…”
Section: Cirrhosismentioning
confidence: 99%
“…A population-based study of Asian patients with chronic liver disease in the United States from 2007 to 2016 found that chronic HBV infection in different Asian populations ranged from 9%-25% in contrast to 0.5% in the general United States population[18]. A nationwide serologic survey of HBV infection in China showed that HBV surface antigen (HBsAg) positivity rates in individuals aged 1-4, 5-14, and 15-29 years were 0.3%, 0.9%, and 4.4%, respectively, in 2014, and these percentages were far lower than the average of 9.8% in 1992 due to the introduction of universal HBV vaccination[59].…”
Section: Risk Factors For Ald In Chinamentioning
confidence: 99%
“…Chronic heavy alcohol consumption may trigger and promote HCC though the generation of carcinogenic aldehydes, reactive oxygen species (ROS), damage-associated molecular patterns (DAMPs), and pathogen-associated molecular patterns, causing oxidative stress that stimulates the inflammatory cascade, inducing the production of tumor-initiating stem cell-like cells, and activating hematopoietic stem cells and immunosuppression[16,17]. Additionally, Asian-Americans had markedly lower ALD-related mortality rates from 2007 to 2016 than non-Hispanic whites[18]. Thus, ALD poses a significant disease burden worldwide.…”
Section: Introductionmentioning
confidence: 99%